Binding additives with sintering action for high-alumina based castables. Issue 12 (15th August 2019) - Consonni, L.B.; Luz, A.P.; Pandolfelli, V.C.
Abstract: Great efforts have been made recently to totally or partially replace calcium aluminate cement (CAC) by alternative materials in refractory castables, in order to attain an enhanced thermomechanical performance of these ceramic linings at intermediate temperatures (600–1200 °C). Besides that, using additives that induce earlier sintering/densification of the refractory microstructure may also reduce the energy costs derived from the production of pre-formed pieces. Based on these aspects, this work investigated the viability of replacing CAC by calcium carbonate (CaCO3 ) or calcium hydroxide [Ca(OH)2 ] to ensure a suitable binding action and effective sintering/densification of the designed compositions at intermediate temperatures. Six high-alumina castables containing these alternative additives or their blend were prepared and their green mechanical strength, apparent porosity and Young's modulus evolution with temperature were evaluated within the 30–1400 °C range. After that, the most promising compositions were characterized via X ray diffraction and thermomechanical tests, such as cold and hot modulus of rupture, thermal shock resistance, etc. Although the selected binders did not result in specimens with green mechanical strength values as high as the ones for the cement-bonded materials (2–8 MPa versus ∼18 MPa, respectively), they could be demolded and handled without any problems. CaCO3 and/or Ca(OH)2 -bonded compositions presented a sintering effect at intermediate temperatures (600–1000 °C) due to the so-called "sintering-coarsening-coalescence" phenomenon. These transformations favored the faster sintering/densification of the tested castables, resulting in samples with improved cold and hot mechanical strength at 900 °C, reaching values within the range of 28–30 MPa instead of 10–13 MPa for the CAC-bonded one. After firing the evaluated compositions at higher temperatures (up to 1500 °C), all compositions presented similar results regarding their modulus of rupture or thermal shock resistance.